64.4.24 problem 23(b)

Internal problem ID [13313]
Book : Differential Equations by Shepley L. Ross. Third edition. John Willey. New Delhi. 2004.
Section : Chapter 2, section 2.2 (Separable equations). Exercises page 47
Problem number : 23(b)
Date solved : Tuesday, January 28, 2025 at 05:21:49 AM
CAS classification : [[_homogeneous, `class A`], _exact, _rational, [_Abel, `2nd type`, `class B`]]

\begin{align*} 2 x^{2}+2 y x +y^{2}+\left (2 y x +x^{2}\right ) y^{\prime }&=0 \end{align*}

Solution by Maple

Time used: 0.085 (sec). Leaf size: 80

dsolve((2*x^2+2*x*y(x)+y(x)^2)+(x^2+2*x*y(x))*diff(y(x),x)=0,y(x), singsol=all)
 
\begin{align*} y &= \frac {-3 c_{1}^{2} x^{2}+\sqrt {3}\, \sqrt {-5 \left (c_{1}^{3} x^{3}-\frac {4}{5}\right ) c_{1} x}}{6 c_{1}^{2} x} \\ y &= \frac {-3 c_{1}^{2} x^{2}-\sqrt {3}\, \sqrt {-5 \left (c_{1}^{3} x^{3}-\frac {4}{5}\right ) c_{1} x}}{6 c_{1}^{2} x} \\ \end{align*}

Solution by Mathematica

Time used: 0.829 (sec). Leaf size: 150

DSolve[(2*x^2+2*x*y[x]+y[x]^2)+(x^2+2*x*y[x])*D[y[x],x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to \frac {1}{6} \left (-3 x-\frac {\sqrt {3} \sqrt {-5 x^3+4 e^{3 c_1}}}{\sqrt {x}}\right ) \\ y(x)\to \frac {1}{6} \left (-3 x+\frac {\sqrt {3} \sqrt {-5 x^3+4 e^{3 c_1}}}{\sqrt {x}}\right ) \\ y(x)\to \frac {1}{6} x \left (\frac {\sqrt {15} x^{3/2}}{\sqrt {-x^3}}-3\right ) \\ y(x)\to \frac {\sqrt {\frac {5}{3}} \sqrt {-x^3}}{2 \sqrt {x}}-\frac {x}{2} \\ \end{align*}